Endoparasite prevalences of the highland sheep in Ethiopia - Bekele, T.; Kasali, O.B.; Wolde-Mariam, W.A. (Elsevier, 1992)
Presents a study conducted in five different sites, Debre Berhan, Dejen, Deneba, Tulu Meko and Wereilu in the highlands of Ethiopia, from June 1988 to December 1989, to determine the prevalences of endoparasites of the highland sheep in Ethiopia. Analyses data to determine nematode log egg counts in different seasons (i.e. long rainy season from June to September, dry season - from October to February and short rainy season from March to May) in the chiefly natural-grazing (Debre Berhan and Tulu Meko) and stubble-grazing (Deneba, Dejen and Wereilu) groups of sheep separately. Data were also analysed by least squares (SAS, 1987) for detecting the effects of grazing differences, age, sex and their interactions on monthly positive nematode log egg counts. Suggests that the transmission of nematodes and trematodes during the long rains and subsequent dry seasons might be controlled by de-worming sheep before the onset of rains to avoid shedding of ova/larvae and contamination of pasture. Water-logged areas should also be avoided to minimize infection.